Saving globalization why globalization and democracy offer the best hope for progress, peace and development - Moore, Mike 1949- (John Wiley & Sons (Asia), 2009)
Globalization is not new, nor is it a policy, it's a process that has existed as long as man looked over the horizon, traveled and traded. It can't be stopped but it can be slowed. It came to a grinding halt in August 1914 and the Marxist detour cost millions of lives and lost three generations their opportunity and hope in many countries. More wealth has been created in the past 60 years than in all of history. After the most successful decade of sustained economic growth in history, this progress is threatened." "Extreme inequality, corruption and environmental degradation threaten the stability and legitimacy of many developing countries' regimes. Anti-globalization and anti-capitalist campaigners' confidence has been emboldened due to the recent economic crisis. Protectionist rhetoric is growing as are the arguments to control and regulate markets. Leaders are meeting to discuss how to face these problems and create a new international architecture. How did we get to this position? What should we do? What is it that determines why some contemporary states are successful while others have failed?" "Saving Globalization attempts to answer these questions by tracing the development of what Moore considers to be "the big ideas of history": democracy, independent courts, the separation of church and state, property rights, independent courts, a professional civil service, and civil society.